Kelembagaan Pemerintahan Desa dan Pemberdayaan Masyarakat Dalam Implementasi Undang-Undang Desa - Suharto, Suharto; Suharto (Jurnal Ilmu Administrasi Negara (JUAN), 2021)
The implementation of the Village Law policy requires support from village government institutions with a pattern of village community empowerment strategies according to existing local potential. The implementation of the Village Law is the hope of all village communities to create an independent village that has an identity, it is an appreciation for the right of the origin of the village with a village community empowerment approach that positions the village community as the main subject / actor not only as an object / target of program activities. village development. This research uses descriptive qualitative research methods, with the aim of finding out how the ability of village government institutions to empower village communities to become independent villages according to the mandate of the Village Law. The successful implementation of the Village Law is significantly influenced by the support of village institutional governance, namely, among others, the Village Government / Village Apparatus, Village Consultative Body (BPD), LPMD / LKMD, PKK, Karangtaruna, BKM / UPK PNPM, Dukuh, RW, RT and other non-governmental groups. The challenge is that institutional performance in accordance with the main tasks of the village's function contributes optimally to the development of the welfare of the village community. So the role of village institutional governance is needed in realizing village empowerment according to the potential, characteristics / local culture of the local village.